1981
DOI: 10.1002/esp.3290060316
|View full text |Cite
|
Sign up to set email alerts
|

The development of blowouts in ‘de blink’, a coastal dune area near Noordwijkerhout, The Netherlands

Abstract: Surface changes in six blowouts in the coastal dunes near Noordwijkerhout between 's-Gravenhage and Zandvoort were measured weekly over a period of two years at 80 erosion pin sites. Readings were correlated with wind variables derived from nearby Valkenburg airbase for the same weekly periods. The values of the wind variables is determined by the number of hours that specific average wind speeds and directions were recorded.The first part of this paper deals with the process of wind erosion. Special attention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1

Year Published

1990
1990
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(37 citation statements)
references
References 3 publications
2
34
1
Order By: Relevance
“…Crinalium epipsammum was isolated from microbial crusts, collected from so-called 'blow outs' (aeolian erosional depressions) on southexposed slopes of sand dunes (Jungerius et al, 1981) in a coastal dune area on the Dutch North Sea coast, which were especially enriched at the edges and centre with this organism. Crust material was suspended in medium BG-11 and incubated at 20 "C under continuous illumination with a photon flux density (PFD) of 40 pmol m-* s-l. after 5 d the enrichment cultures were plated on BG-11 medium solidified with I % (w/v) agar (Difco Bacto).…”
Section: Methodsmentioning
confidence: 99%
“…Crinalium epipsammum was isolated from microbial crusts, collected from so-called 'blow outs' (aeolian erosional depressions) on southexposed slopes of sand dunes (Jungerius et al, 1981) in a coastal dune area on the Dutch North Sea coast, which were especially enriched at the edges and centre with this organism. Crust material was suspended in medium BG-11 and incubated at 20 "C under continuous illumination with a photon flux density (PFD) of 40 pmol m-* s-l. after 5 d the enrichment cultures were plated on BG-11 medium solidified with I % (w/v) agar (Difco Bacto).…”
Section: Methodsmentioning
confidence: 99%
“…Spatial differences in sand transport influence the patterns of erosion and deposition within blowouts and play an important role in their morphological development. Sediment transport within blowouts has been measured using erosion pins (Jungerius et al, 1981;Jungerius and Meulen, 1989;Jungerius et al, 1991;Pluis, 1992;Byrne, 1997;Hugenholtz and Wolfe, 2009), sand traps (Gares, 1992;Byrne, 1997) and topographic surveys (Gares and Nordstrom, 1988;Käyhkö, 2007). However, only Smyth et al (2014) have measured sediment transport in relation to near surface wind speed within a coastal trough blowout; they found that where airflow was steadiest, sediment transport rate was greatest.…”
Section: Introductionmentioning
confidence: 98%
“…Wind erosion along the Dutch North Sea coast has been studied fairly extensively over the past 20 years, with a view to arriving at sound management practices of the coastal zone (Van Bohemen, 1990). Examples of subjects of study in the coastal zone are the development of blowouts in the coastal dunes (Jungerius et al, 1981;Jungerius and Van der Meulen, 1989; Van den Ancker et al, 1985;Pluis, 1993), the testing of an acoustic sediment sensor (Spaan et al, 1991), the sand budget of the foredunes (Arens, 1994), the aeolian transport of beach nourishment sand (Van der Wal, 1999) and the modelling of air flow and sand transport across transverse dunes . A main issue in coastal management is stabilization versus so-called 'dynamic' or 'integrated' management of the coastal zone, coastal defence and safety being only one of the management aims.…”
Section: Wind Erosionmentioning
confidence: 99%